2006
DOI: 10.1590/s0100-879x2006005000021
|View full text |Cite
|
Sign up to set email alerts
|

Inducible nitric oxide synthase and tumor necrosis factor-alpha in delayed gastric emptying and gastrointestinal transit induced by lipopolysaccharide in mice

Abstract: Gastrointestinal motility disturbances during endotoxemia are probably caused by lipopolysaccharide (LPS)-induced factors: candidates include nitric oxide (NO), tumor necrosis factor-α (TNF-α), interleukin-1ß, and interleukin-6. Flow cytometry was used to determine the effects of LPS and these factors on gastric emptying (evaluated indirectly by determining percent gastric retention; %GR) and gastrointestinal transit (GIT) in male BALB/c mice (23-28 g). NO (300 µg/mouse, N = 8) and TNF-α (2 µg/mouse, N = 7) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2009
2009

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…LPS stimulates host cells and leads to the production of inflammatory mediators including cytokines [2], chemokines [3], and lipid metabolites [4]. When administered to mice, LPS alone is sufficient to cause septic shock [5]. Unlike Gram-negative bacteria, Gram-positive bacteria lack LPS and instead contain lipoteichoic acid (LTA) on their cell wall [6].…”
Section: Introductionmentioning
confidence: 99%
“…LPS stimulates host cells and leads to the production of inflammatory mediators including cytokines [2], chemokines [3], and lipid metabolites [4]. When administered to mice, LPS alone is sufficient to cause septic shock [5]. Unlike Gram-negative bacteria, Gram-positive bacteria lack LPS and instead contain lipoteichoic acid (LTA) on their cell wall [6].…”
Section: Introductionmentioning
confidence: 99%
“…126,127 IL-1 and TNF-␣ also inhibit gastric emptying. 124,126,127,135 Additionally, Kanoski and colleagues 136 found that adiposity signal leptin and the brain-gut hormone cholecystokinin (CCK) work together in the producing sensation of "satiety. "…”
Section: Anorexia Cytokines and Neurochemicalsmentioning
confidence: 99%
“…In healthy volunteers, the NO donor nitroglycerin has been shown to accelerate gastric emptying [23]. In mice, however, exogenous NO has been shown to delay gastric emptying (gastric emptying was measured as the retention of fluorescent microbeads 30 min after administration of a liquid meal [24]), whereas in our study the NO donor Atropine (1 mg kg -1 ) and molsidomine (40 mg kg -1 ) were administered subcutaneously while L-NAME was dissolved in the drinking water (0.85 mM) 48h before the start of the experiment molsidomine did not alter food retention in the stomach. These divergent results in mice could be because of different methodologies.…”
Section: Gastric Emptying and Motilitymentioning
confidence: 99%